Scotland - Zobel, Derek, 1983- (Minneapolis, MN : Bellwether Media, 2012)
Introduces young readers to the geography and culture of Scotland.
Includes bibliographical references (p. 31) and index.
4.8
K-3.
K-3
Keywords: Scotland -- Juvenile literature; Scotland; Scotland; Readers (Elementary).